FORCED DEGRADATION STUDY OF ENALAPRIL MALEATE AND ITS COMPATIBILITY STUDY WITH THE SELECTED EXCIPIENTS (International Journal of Food and Nutritional Sciences, 2022)
Enalapril maleate's physicochemical stability was examined in the presence of fourteen distinct excipients categorized into four groups. The degree of a drug-excipient interaction was examined by using HPLC to monitor the chemical stability. It was discovered that enalapril maleate's stability follows a certain sequence. The following combinations kept enalapril maleate the most stable: disaccharides, celluloses, starches, and superdisintegrants. The properties of the excipient may have an impact on the rate of deterioration. A material's particle surface is more reactive when it has a lower crystallinity and a greater water sorption capacity. The breakdown of enalapril maleate was shown to be caused by the condensation layer that formed on the excipient's surface. By altering the excipient's surface and the humidity of the surrounding air, a mechanism was discovered that permitted a changeable accumulation of the condensation layer. The microenvironmental pH for this particle-particle interaction only has a little impact since it wasn't determined to be a deciding factor for degradation. Furthermore, there seems to be a strong correlation between the excipients' water sorption activity and the breakdown of enalapril maleate.